Austronesian Houses: The Architectural Characteristics Linkage Between Batanghari Hulu Traditional Houses with Tanah Datar's Rumah Gadang - Muhammad Khamdevi; Iqbal Rasyid Nasution (Universitas Bandar Lampung (UBL), 2014)
The region of Central Sumatra (West Sumatra, Eastcoast of Sumatra, Bengkulu, and Jambi) has shared history from the kingdom periods of Kantoli (Akhandalapura), Srivijaya, Dharmasraya, Malayupura, Pagaruyung, Johor-Riau, and Jambi-Palembang. The houses in the Batang Hulu region seem to have similarities with the Rumah Gadang in the Rantau and Darekof Tanah Datar areas. There is no research that has tried to study the linkage among them. Therefore, this study tried to investigate theirarchitectural characteristics linkage.The qualitative method is used by the houses characteristics comparing from the data collected in the field. The study resulted a strong indicationofcharacteristics linkage between the houses, in term of space, shape-form, and style.